2013 IEEE/RSJ International Conference on Intelligent Robots and Systems 2013
DOI: 10.1109/iros.2013.6696874
|View full text |Cite
|
Sign up to set email alerts
|

A compliant humanoid walking strategy based on the switching of state feedback gravity compensation controllers

Abstract: This paper provides stability analyses for two different types of desired gravity compensation controllers, employing both motor and link feedback, and describes a means by which these controllers can be used to control a compliant humanoid robot in order to ensure the successful execution of walking trajectories. Given the challenging task of controlling compliant bipedal systems, owing to their possession of under-actuated degrees of freedom, the full actuator and link dynamics are accounted for. The propose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Using control law (5), the closed-loop system was rendered globally asymptotically stable, as was demonstrated in the analysis presented in [23]. Hence, the following Lyapunov function shall be considered throughout the paper:…”
Section: Closed-loop System Lyapunov Functionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using control law (5), the closed-loop system was rendered globally asymptotically stable, as was demonstrated in the analysis presented in [23]. Hence, the following Lyapunov function shall be considered throughout the paper:…”
Section: Closed-loop System Lyapunov Functionmentioning
confidence: 99%
“…where has been replaced with since we are considering a desired gravity compensation controller, while ( ) + denotes the Moore-Penrose pseudoinverse of . By considering the closed-loop system's steady state equations, we can define the following matrix that plays a central role in the stability analysis since it must satisfy certain conditions in order for closed-loop stability to be guaranteed, as shown in [23]:…”
Section: B Desired Gravity Compensation Controllermentioning
confidence: 99%
See 1 more Smart Citation
“…A method by which the GRFs can be translated into joint torques is described by [26], mathematically proving this specific controller's passivity. The method proposed in this paper is an extension to the work seen in [9], which involves the use of PDD control (motor position, motor velocity and link velocity feedback) on 6 degree-offreedom (DOF) SS and 3-DOF DS models of the robot, in combination with gravity compensation control. The mathematical models describe the full compliant dynamics (the motor and link dynamics appearing before and after the elastic element), thereby accounting for the mere sagittal elements, since it is only those joints that comprise Series Elastic Actuators (SEA).…”
Section: Accepted Manuscript N O T C O P Y E D I T E Dmentioning
confidence: 99%
“…Its intrinsic compliance, due to the passive elasticity in its joints, makes this robot a good candidate for this kind of task. In previous works [6], [7], [8] we focused on the effects of compliance on the dynamics of walking. It was demonstrated that compliance can reduce the effect of disturbances due to the take off and landing of the foot.…”
Section: Introductionmentioning
confidence: 99%